ZMYND8 suppresses MAPT213 LncRNA transcription to promote neuronal differentiation - Santanu Adhikary; Vipin Singh; Ramesh Choudhari; Barbara Yang; Swagata Adhikari; Enrique I. Ramos; Soumi Chaudhuri; Siddhartha Roy; Shrikanth S. Gadad; Chandrima Das (Cell Death and Disease, 2022)
Abstract Zinc Finger transcription factors are crucial in modulating various cellular processes, including differentiation. Chromatin reader Zinc Finger MYND (Myeloid, Nervy, and DEAF-1) type containing 8 (ZMYND8), an All-Trans Retinoic Acid (ATRA)-responsive gene, was previously shown to play a crucial role in promoting the expression of neuronal-lineage committed genes. Here, we report that ZMYND8 promotes neuronal differentiation by positively regulating canonical MAPT protein-coding gene isoform, a key player in the axonal development of neurons. Additionally, ZMYND8 modulates gene-isoform switching by epigenetically silencing key regulatory regions within the MAPT gene, thereby suppressing the expression of non-protein-coding isoforms such as MAPT213. Genetic deletion of ZMYND8 led to an increase in the MAPT213 that potentially suppressed the parental MAPT protein-coding transcript expression related to neuronal differentiation programs. In addition, ectopic expression of MAPT213 led to repression of MAPT protein-coding transcript. Similarly, ZMYND8-driven transcription regulation was also observed in other neuronal differentiation-promoting genes. Collectively our results elucidate a novel mechanism of ZMYND8-dependent transcription regulation of different neuronal lineage committing genes, including MAPT, to promote neural differentiation.